2010
DOI: 10.4269/ajtmh.2010.10-0074
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant AeDNA Containing the Insect-Specific Toxin, BmK IT1, Displayed an Increasing Pathogenicity on Aedes albopictus

Abstract: Abstract. The Aedes aegypti densovirus (AeDNV) has previously shown potential in mosquito control. To improve its efficacy as a biopesticide, the gene for an excitatory insect-specific toxin from Buthus martensii Karsch (BmK IT1) was inserted into the AeDNV genome and cloned into pUCA plasmid. The coding sequence for green fluorescent protein was ligated to the C-terminus of the BmK IT1 gene as a screening marker. Recombinant and helper plasmids were cotransfected into C6/36 cells; wild-type viruses were the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…It is worth mentioning that densoviruses have some features that make them attractive for use as biological control agents (103). In fact, developing genetically modified densoviruses to express genes of interest and their successful application in vitro has been discussed as an alternative approach to control mosquito populations (103)(104)(105).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that densoviruses have some features that make them attractive for use as biological control agents (103). In fact, developing genetically modified densoviruses to express genes of interest and their successful application in vitro has been discussed as an alternative approach to control mosquito populations (103)(104)(105).…”
Section: Discussionmentioning
confidence: 99%
“…Their stability, narrow host range, and pathogenicity make DNVs attractive as bio-pesticides (Carlson, Suchman & Buchatsky, 2006; Suzuki et al, 2015). In mosquitoes, Aedes aegypti densovirus (AeDNV) has been intensively studied as a transducing vector and biocontrol agent against Aedes mosquitoes (Allen-Miura et al, 1999; Ledermann et al, 2004; Gu et al, 2010). We recently reported that An.…”
Section: Introductionmentioning
confidence: 99%
“…Anal papillae are the major portal of entry of AeDNV, with dissemination to the whole body occurring from there [16]. However, in some cases the anal papillae present a barrier to virus dissemination, in which case the infection remains restricted to the anal papillae.…”
Section: Resultsmentioning
confidence: 99%